Detection of TERT promoter mutation in serum cell‐free DNA using wild‐type blocking PCR combined with Sanger sequencing in hepatocellular carcinoma. Issue 12 (1st March 2020) - Akuta, Norio; Suzuki, Fumitaka; Kobayashi, Mariko; Fujiyama, Shunichiro; Kawamura, Yusuke; Sezaki, Hitomi; Hosaka, Tetsuya; Kobayashi, Masahiro; Saitoh, Satoshi; Arase, Yasuji; Ikeda, Kenji; Suzuki, Yoshiyuki; et al.
Abstract: Telomerase reverse transcriptase ( TERT) promoter mutation is the most frequent genetic alteration in hepatocellular carcinoma (HCC). However, there is currently no suitable highly sensitive method that can detect such mutation using serum cell‐free DNA (cfDNA). We analyzed somatic point mutations that substitute cytosine for thymidine at position 228 (C228T), as one of the hotspots of TERT promoter mutations, in serum cfDNA using a highly sensitive detection method of wild‐type blocking polymerase chain reaction (WTB‐PCR) combined with Sanger sequencing. In TERT promoter mutation sensitivity study, synthetic oligonucleotides were prepared to determine the lowest detection limit of the WTB‐PCR, using serial dilutions of mutant‐type (MT) DNA in the background of wild‐type (WT) DNA. Using this technique, we conducted a longitudinal study in one patient who developed HCC during the follow‐up and determined the relationship between HCC and TERT C228T in serum cfDNA. In the sensitivity study, the mutant peak at position 228 was detected at 0.7% or higher but was not detected at 0.6%. Thus, sequencing analysis of WTB‐PCR product demonstrated the limit of detection in excess of 0.7% MT DNA in the background of WT DNA. One male patient with HCV‐related cirrhosis developed HCC during the follow‐up. TERT C228T was negative before the diagnosis of HCC, positive at the diagnosis of HCC and did not increase with advancement of malignancy. We developed a highly sensitive method for detection of TERT promoter mutation using WTB‐PCR combined with Sanger sequencing and demonstrated its clinical usefulness in the measurement of TERT C228T in serum cfDNA. Larger studies are needed to confirm these results and establish the clinical utility of this new method. Research Highlights: We developed a highly sensitive method for detection of TERT promoter mutation using WTB‐PCR combined with Sanger sequencing and demonstrated its clinical usefulness in the measurement of TERT C228T in serum cfDNA.